EFFECT OF WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH WORK SPIRIT AS INTERVENING VARIABLE - Limega Candrasa (Bajang Institute, 2022)
This research shows. (1) It can be seen that the magnitude of the adjusted R square value is 0.130 or 13.0%. This shows that the work environment (X) can explain work morale (Z) by 13.0%, the remaining 87.0% (100% - 13.0%) is explained by other variables outside the research model. (2) The results of the t-test (partial) can be seen that the obtained tcount (7.652) > ttable (2.042), as well as the significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the work environment variable (X) positive and significant effect on morale (Z). (3) The results of the t-test (partial) can be seen that the value of tcount (3.955) > ttable (2.042), and the significance value of 0.00 <0.05, it can be concluded that the second hypothesis is accepted, meaning that the work environment (X) has a significant effect on employee performance (Y). (4) The results of the path analysis test show that the direct effect of variable X on variable Y2 is 0.586. Meanwhile, the indirect effect through the X variable is 0.397 x 0.184 = 0.730. From the calculation results obtained, the indirect effect through the Z variable is greater than the direct effect on the Y variable.